Effectiveness of electroacupuncture on anxiety: a systematic review and meta-analysis of randomized controlled trials - Hong, Wan ki; Kim, Yeon Ji; Lee, Ye rim; Jeong, Hye In; Kim, Kyeong Han; Ko, Seong-Gyu (Frontiers in Psychology, 2023)
This systematic review and meta-analysis aimed to comprehensively evaluate the effectiveness of electroacupuncture (EA) for patients with anxiety. Randomized controlled trials (RCTs) on the treatment of anxiety by EA up to November 2022 were searched and collected from nine databases. Hamilton Anxiety Rating Scale (HAMA), self-rating anxiety scale (SAS), and adverse reactions were used as outcome indicators. The quality of relevant articles was evaluated using the Cochrane Collaboration's risk of bias tool. The quality of evidence for each outcome was classified as "low risk", "unclear risk", or "high risk." RevMan 5.0 was used for data analysis. A total of 633 articles were identified from nine electronic databases; 37 RCTs were included, which measured anxiety changes by using EA alone compared to the control group. For the main outcome, EA significantly reduced the HAMA score (Mean difference(MD):−1.13 (95% CI:−2.55-0.29), I²:80%), and the quality of evidence was moderate. EA significantly reduced the SAS score (MD:−3.47 (95% CI:−6.57-−0.36), I²:88%), and the quality of evidence was moderate. Our meta-analysis shows that EA reduces HAMA and SAS. This study suggests that EA can relieve anxiety. For various uses, additional research is needed on its effect when combined with other treatments.